(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study employs qualitative research methodology, utilizing a documentary approach to gather data. The data for this brief study consists of selected dialogues and narrative structures. Additionally, gazettes, journals, hypotheses, treatises, other books, and URLs are used as sources of data. An inductive method is employed to analyze the dilemmas, presenting communication of ideas in the analysis from the specific to the general. Paulo Coelho makes the most of his writer’s liberation by selecting to commence upon individualism. The stable theme in The Alchemist is to follow your dreams by following what your heart yearns. During the young boy’s expedition, he learns to listen to the compassion and to follow the sacramental investigation as a process of following your dreams. Paulo Coelho’s the Alchemist is a hypnotizing myth about the spiritual journey we must all take to accomplish our dreams and play out our fates. Along the way, we need to learn how to certitude others, to interpret the world for signs of God, to listen to our heart, to make the most of concurrency and good fortune. To sum up, it can be concluded that Paulo Coelho embodies Orientals through the representation of the West and the East.